VIEWS ON GENDER EQUALITY IN THE WORK “THE ORIGIN OF THE FAMILY, PRIVATE PROPERTY AND THE STATE” AND ITS SIGNIFICANCE FOR VIETNAM - Huong, Tran Thi (Veredas do Direito, 2025)
The article aims to clarify the views on gender equality expressed in Friedrich Engels's The Origin of the Family, Private Property and the State. The hypothesis is whether the role and status of women have changed over historical periods. To clarify the purpose and hypothesis, the author focuses on clarifying issues such as: analyzing the deep roots of the existence of gender inequality and explaining the changes in the status of women over historical periods; clarifying the origins leading to gender inequality and the way to shorten the gender gap according to Friedrich Engels's point of view. Pointing out the significance of women's liberation, ensuring gender equality in all areas of life in Vietnam today.